Manajemen Program Pendidikan Hafizh Qur'an Dalam Peningkatan Hafalan Al-Qur'an Siswa Di SMP Al-Hikmah Medan Marelan - Nadia Siregar, Fatin (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
This study aims to determine the process of planning, organizing, directing and evaluating the Tahfidz Al-Quran program at Al-Hikmah Middle School, Medan Marelan. The research objectives in this case are: 1) Explaining the planning process carried out by Al-Hikmah Junior High School 2) To find out the process of organizing the Quran tahfidz program at Al-Hikmah Junior High School. 3) To find out how to direct and evaluate the Quran tahfidz program at Al-Hikmah Junior High School. The research method used is qualitative research. After conducting research with several methods above, the results obtained are that: 1) The concept that has been arranged well because of good planning as well. With this plan, it can make it easier for teachers to carry out supervision and evaluation of the running of the Quran tahfidz program at Al-Hikmah Middle School 2) The organization carried out by Al-Hikmah Junior High School is by choosing teachers according to their fields in order to achieve the goals of students and students in memorizing Al-Quran 3) The direction is to build a cooperative relationship between the foundation and the school principal in motivating and providing regular student memorization reports to find out the progress and success of the Al-Quran tahfidz program. 4) the evaluation is done by holding an exam, therefore it can be known through the results of student and student exams. The standard of achievement for students can be seen from their ability to read the Al-Quran well, understand the tajwid and memorize the Qur'an quickly